Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Li, Yi-Wen; Wang, Chung-Hsing; Chen, Chao-Jung; Wang, Charles C. N.; Lin, Cheng-Li; Cheng, Wai-Kok; Shen, Hsin-Yi; Lim, Yun-Ping (Archives of toxicology, 2018)
To characterize the association between epilepsy, use of antiepileptic drugs (AEDs), and the risk of hyperlipidemia, we conducted a nationwide population-based cohort study with data obtained from the National Health Insurance Research Database of Taiwan. The effects of AEDs on lipogenic gene expression were also examined in vitro. We identified 3617 cases involving patients, whose epilepsy was newly diagnosed between 2000 and 2011, and selected a comparison cohort comprising 14,468 patients without epilepsy. The Cox proportional hazards model was used to evaluate the association between epilepsy, AED use, and hyperlipidemia. The incidence rate of hyperlipidemia was higher in the epilepsy cohort than in the comparison cohort, with an adjusted hazard ratio (aHR) of 1.21 [95% confidence interval (CI): 1.06–1.38] after adjusting for comorbidities and medications. Epilepsy patients not taking AEDs had a higher risk of hyperlipidemia (aHR 1.65; 95% CI 1.35–2.03). Among AEDs, only valproate treatment showed a higher risk of hyperlipidemia (aHR 1.53; 95% CI 1.01–2.33), although the dose-dependent effect did not reach statistical significance. In vitro studies with two hepatic cell lines showed that valproate may exert its effects by activating the liver X receptor alpha (LXRα) signaling pathway, inducing the expression of lipogenesis-related genes and increasing cellular lipid contents. In silico calculations concluded that valproate can bind stably with the ligand-binding domain of LXRα. Thus, valproate-induced hepatic lipogenic gene expression may occur through LXRα activation. Predicting the ‘off-target’ effects of valproate may prove valuable in developing antiepileptic agents with fewer adverse reactions. Monitoring blood lipid levels throughout the course of treatment is recommended.